2011
DOI: 10.1111/j.1600-0463.2011.02751.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of omega-3 fatty acid supplements in sickle cell disease

Abstract: In a previous retrospective study, it was observed that the greater the amounts of the omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the blood, the lesser the number of complications of sickle cell disease (SCD) and the higher the steady state haemoglobin level. SCD causes ischaemia-reperfusion injury and inflammation; which can be ameliorated by a metabolite of DHA that down-regulates expression of pro-inflammatory genes. The objectives of this prospective pilot study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…On the other hand, treatment with n−3 fatty acids resulted in lower but not significant levels of CRP or platelet count compared to untreated patients. This finding is consistent with results reported from studies on healthy adults [35], patients with chronic nonautoimmune disease [36] and SCD patients [37]. It is possible that a larger sample size is needed to elucidate the effect of supplementation on variables of huge inter-individual variations such as platelet count.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, treatment with n−3 fatty acids resulted in lower but not significant levels of CRP or platelet count compared to untreated patients. This finding is consistent with results reported from studies on healthy adults [35], patients with chronic nonautoimmune disease [36] and SCD patients [37]. It is possible that a larger sample size is needed to elucidate the effect of supplementation on variables of huge inter-individual variations such as platelet count.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, SCD patients with PHT have higher levels of markers of endothelial activation, coagulation activation and other inflammatory markers than SCD patients without PHT. Hence the clinical importance of the findings of this study, besides supporting previous reports about the positive therapeutic effect of n − 3 fatty acids in SCD [16,18,19,37], that it suggests high DHA n − 3 supplement as a potential intervention to prevent PHT, stroke and other SCD vasculopathy-related complications.…”
Section: Discussionsupporting
confidence: 88%
“…Recent reports on the beneficial effects of ω-3 fatty acid supplementation on the human hematologic phenotype of SCD suggest a possible therapeutic effect of ω-3 fatty acids in SCD. [12][13][14] The present work provides evidence for several relevant mechanisms underlying this potential benefit. We propose that the beneficial role of ω-3 PUFA on SCD vascular dysfunction might be exerted: (i) directly through the reduction of ET-1 expression, which is involved in adaptive inflammation, expression of adhesion molecules such as VCAM-1, and neutrophil chemotaxis; 46 and (ii) indirectly through reduced inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 81%
“…10,11 Recently, human studies have demonstrated that supplementation of SCD subjects with fish oil containing ω-3 fatty acids reduces VOC, pain episodes, and blood transfusions. [12][13][14] To date, however, there are insufficient clinical and molecular data to support routine dietary supplementation with fish oil for SCD patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Ren et al [5658] demonstrated that humans with SCD have decreased omega-3 fatty acids and increased arachidonic acid (an omega-6 fatty acid) in the RBC membrane. To date, trials in humans with SCD have indicated that dietary supplementation with omega-3 fatty acids may reduce severe anemia, vaso-occlusive pain episodes, white blood cell count, and prothrombotic activity [18;52;64]. Of note, these trials did not assess the effect of DHA on RBC structural and functional characteristics.…”
Section: Introductionmentioning
confidence: 99%